Daratumumab: A drug with transfusion dilemma - Amit Kumar Biswas; Anurag Gairola; Ajay Kumar Baranwal; Rajat Jagani; Amit Ajay Pawar; Ujjwal Dimri (Global Journal of Transfusion Medicine, 2023)
Daratumumab (DARA) is an anti-CD38 monoclonal antibody which has promising results in relapsed and refractory multiple myeloma (RRMM). DARA interferes with blood compatibility testing by causing incompatible results while crossmatching by antihuman globulin phase and presenting as a panagglutination picture in the indirect antiglobulin test. Immunohematology workup must be done to rule out allo- or autoantibody and to issue compatible unit to the patient as transfusion support is vital for all these patients and must not be delayed. Here, we present a case report of one such patient who was undergoing treatment with DARA for RRMM and had incompatibility found during crossmatching. Out of the available methods to resolve this problem, we utilized the treatment of red cells with 2-mercaptoethanol at our blood center which was effective, time saving, feasible, and less resource demanding. During the progressive course of disease, our patient required transfusion on a regular basis, and we were able to provide compatible units on each instance utilizing the same technique.